Arqus University Alliance Staff Members’ Linguistic and Intercultural Needs: Survey Results - Klinge, Simone; Gödeke, Barbara (Verbum, 2022)
The Arqus European Higher Education Alliance identified as one of its priorities the development of linguistic and intercultural competences of university staff as a measure to ensure high quality teaching and services to students and staff. The present paper presents the main results of a questionnaire that was sent to all academic and administrative staff of the alliance member universities in May and June 2021 that asked about their linguistic and intercultural training needs. The findings of the results were intended to guide actions within the language policy of the universities and serve as a basis for designing joint workshops for staff members according to their needs. The overwhelming majority of the 2206 staff members that completed the questionnaire deemed intercultural training and language training necessary for their professional activity. The languages indicated were wide in range, whereby English clearly stood out, reflecting its growing importance as the lingua franca in academia.